Childhood Overweight and Obesity and Associated Factors in Iranian Children and Adolescents: A Multilevel Analysis; the CASPIAN-IV Study - Khashayar, Patricia; Kasaeian, Amir; Heshmat, Ramin; Motlagh, Mohammad Esmaeil; Mahdavi Gorabi, Armita; Noroozi, Mehdi; Qorbani, Mostafa; Kelishadi, Roya (Frontiers in Pediatrics, 2018)
Objective- The purpose of this paper is to explore multidimensional factors related to obesity based on the data gathered on different aspects of the general health status were assessed among a large number of Iranian children and adolescents in the fourth phase of the “Childhood and Adolescence Surveillance and Prevention of Adult Non-communicable disease” survey. It also aims to determine the degree to which each ecological context contributes to childhood overweight/obesity. Method- A total of 14,880 students and their parents were recruited. They filled out a questionnaire on their relationship with peers, body image, and psychosocial environment of school, dietary habits, life-style habits, physical activity pattern and socioeconomic status. Their height, weight, waist, hip and wrist circumferences as well as blood pressure was also measured. Multilevel modeling using a three-level random intercept linear regression model for BMI and two three-level random intercept logistic regression models for overweight and obesity were used. In our hierarchical models, children (first level) were conceptualized as being nested within provinces (second level) and provinces within quad regions (third level). Result- From among the 13486 recruited students, 9.7% were overweight and 11.9% were obese. From among the studied predictors, positive family history of obesity (OR =2.04, P <.001), SES status (high/low) (OR = 1.89), and birth weight (4kg+/2.5kg-) (OR= 1.8, P <0.001) had the highest effects on the odds of becoming obese. Increasing age was the only factor in the obesity model that had a significant preventive effect on the odds of becoming obese (OR=0.96, P<0.001). Conclusion- The results of the present study may help policymakers to provide a theoretical basis and model childhood obesity as a function of both individual and external factors deriving from both family and school.